Optimalisasi Serah Terima antar Ruangan dan Transfer Pasien Kasus COVID-19 ke Ruang Perawatan - Galleryzki, Annisa Rahmi; Hariyati, Rr. Tutik Sri; Anisah, Siti; Pratiwi, Leny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to provide recommendations for the implementation of COVID-19 patient transfers and handovers between rooms carried out by nurses to be more optimal. The method used is a case study at the Jakarta Military Hospital. The results of the study through interviews and document searches found that in the planning function, there is no SOP for handovers between rooms, the SOP for handovers between rooms is combined with the SOP for handovers between shifts where the SOP contains more of the handover process between shifts. In addition, there is no monitoring and evaluation (money) form for the implementation of handovers and documentation of handovers between rooms. In conclusion, the situation analysis obtained at the Jakarta Military Hospital, the handover process between rooms, and the COVID-19 patient transfer process still needs to be developed. Keywords: COVID-19, Handover, Intrahospital Transfer, Patient Transfer